YANGTZE DYKE AND ITS STRENGTHENING - G. - X. Li; Y. - X. Jie; Q. - Y. Li (Lowland Technology International, 2003)
Levees play important role in flood prevention. More than 30,000 km length of levees protect the rich and populous plain regions of the middle and lower reaches of Yangtze River. However, the quality of the levee varies greatly in different regions. This paper summarizes the characteristic of Yangtze dyke, its main dangerous situations and hidden defects, together with the measures for handling these problems.